Kinerja Industri Manufaktur di Provinsi-Provinsi Sumatera Tahun 2010-2015 [Manufacturing Industry Performance in Sumatra Provinces 2010-2015] - Juli Panglima Saragih (Jurnal Ekonomi & Kebijakan Publik, 2018)
Manufaturing industry has given significant contribution to Indonesia’s gross domestic product since 2005-2010. Most of manufacturing industry in Sumatera island were mainly represented by agroindustry, and oil and gas industries. This research aims to analyze manufacturing industry performance in Sumatera island in terms of its share in Sumatra GDP and comparing it to total production of national manufacturing industry. This study uses Location Quotient methods to analyse contribution of manufacturing industry on Sumatra GDP. This study finds that Location Quotient of manufacturing industry of Sumatera island is overall less than 1 in period of 2010-2015. It indicates that manufacturing industry in Sumatra gives less significant contribution to overall of GDP of Sumatra. However, in terms of provinces in Sumatera island, the highest shares of manufactuting industry to GDP were in three provinces, namely, North Sumatra, Riau islands, and Riau provinces. Whilst in other provinces in Sumatra, the shares of industry to GDP were moderate and small. This study suggests that to improve the shares of industry in Sumatera island to GDP, the government must diversify its manufacturing industries from natural resource base to other local specific base resources. These findings should be accommodated in future policy to improve the economic growth in Sumatera island in particular and Indonesia in general. Keywords: manufacturing industry, Location Quotient, performance of industry sector, gross domestic product, Sumatera IslandAbstrakIndustri manufaktur merupakan salah satu sektor penting dalam perekonomian nasional. Kontribusinya semakin meningkat terhadap PDB selama periode tahun 2005-2010. Industri manufaktur di Pulau Sumatera sebagian besar berbasis perkebunan, sumber daya alam (SDA), minyak, dan gas bumi. Penelitian ini bertujuan mengkaji dan menganalisis kinerja industri manufaktur di Pulau Sumatera dengan menggunakan metode analisis Location Quotient (LQ). Estimasi penghitungan LQ menggunakan data-data industri manufaktur se-Sumatera dalam periode tahun 2010-2015. Dari hasil analisis LQ tersebut diperoleh antara lain bahwa industri manufaktur di Pulau Sumatera periode tahun 2010-2015 memiliki nilai LQ ˂ 1. Ini menunjukkan secara agregat industri manufaktur di Pulau Sumatera masih belum dapat diandalkan untuk percepatan pertumbuhan ekonomi (PDB) regional Pulau Sumatera walaupun berkontribusi positif terhadap industri manufaktur nasional. Namun jika berdasarkan LQ provinsi, industri manufaktur tumbuh signifikan hanya terjadi di tiga provinsi, yakni Provinsi Sumatera Utara, Kepulauan Riau, dan Riau. Sedangkan dua provinsi, yakni Provinsi Sumatera Selatan dan Lampung ditemukan memiliki pertumbuhan moderat. Lima provinsi lainnya mengalami pertumbuhan yang sangat lambat dalam periode yang sama. Antara pulau di Indonesia, kontribusi industri manufaktur Pulau Sumatera relatif besar setelah Pulau Jawa dibandingkan dengan pulau lain di luar Pulau Jawa. Oleh karena itu, solusi yang dapat ditempuh adalah perlunya diversifikasi industri di Pulau Sumatera sesuai potensi sumber daya yang dimiliki untuk memperkuat struktur industri manufaktur di Pulau Sumatera tersebut. Diversifikasi industri dimaksud tidak hanya industri berbasis perkebunan dan sumber daya alam. Kebijakan industri nasional ke depan selayaknya memerhatikan temuan studi ini supaya pertumbuhan industri di Pulau Sumatera semakin optimal.Kata kunci: industri manufaktur, kinerja sektor industri, Produk Domestik Bruto, Sumatera